PENERAPAN METODE SYI’IR PEGO DALAM MENINGKATAKAN HASIL BELAJAR KEMAMPUAN MENULIS (KITABAH): (Studi Kasus MI Sayyid Abdurrohman I Pagerwojo) - Zuni Humairoh; Arina Maulidia Agustin (Abnauna: Jurnal Ilmu Pendidikan Anak, 2022)
Syi'ir is a series of neatly arranged sentences that are sounded with a certain rhythm to make it easier for readers to feel their uniqueness and more or less understand the meaning of the sentences they read. The focus of the problem in this study are: (1) How is the application of the Syi'ir Pegon method at MI Sayyid Abdurrohman I Pagerwojo?, (2) How are the learning outcomes of writing skills (kitabah) for class 3 students of MI Sayyid Abdurrohman I Pagerwojo?, (3 ) How is the application of the Syi'ir Pegon method to improve the learning outcomes of writing skills (kitabah) for grade 3 students of MI Sayyid Abdurrohman I Pagerwojo?. The research in this thesis uses classroom action research (CAR) research which is carried out collaboratively. Data collection techniques used are tests, observation techniques (observation), interviews, field notes, and documentation. The results of this study indicate that: (1) The application of the Syiir method at MI Sayyid Abdurrohman I Pagerwojo, namely First, the teacher gives examples of pronunciation of lafadz and students listen carefully. Second, students imitate the lafadz syiiran that has been exemplified by the teacher. Third, between students, continue to connect lafadz lafadz the number of body members in pego with syiiran. (2) Learning outcomes of writing skills (Kitabah) by applying the Syiir Pego method. The results of this study can be seen from the average cycle I and II, and the research can be seen from the completeness of learning to write (Kitabah) in cycle II which has reached the success criteria, namely 75% of students achieved a test score of 68 (scale 1-100) and the average class in the first cycle is 63.65, the average in the second cycle is 72.85 reaching a score of 68 (scale 1-100), and in cycle 3 the average in the second cycle is 100 reaching a score of 68 (scale 1-100 ). (3) The application of the Syiir Pego method to improve learning outcomes of writing skills (Kitabah) for class III at MI Sayyid Abdurrohman I Pagerwojo In cycle 1, it is in the Practicing Again category. and. In cycle 2, it is categorized as very good. While the assessment of the first cycle reached a value of 66.66%, the second cycle reached a value of 93.33%, the third cycle reached a value of 100%, so the research increased from cycle 1 to cycle 2, and cycle 2 to cycle 3.